Solid phase synthesis and thioether ligation of hairpin peptides from single-pass transmembrane receptors. - Surya, Wahyu. (2010)
Integrins and fibroblast growth factor receptors (FGFR) are important members of single-pass transmembrane receptors. The transmembrane domains held particular importance in the signaling activity of these receptors. The structural features that govern the interaction between transmembrane domains of these receptors are not fully known yet. To study these transmembrane domains, transmembrane peptides that contains 13C=18O-labeled amino acid were synthesized by means of FMOC-based solid phase synthesis. Onto the N-terminus of one peptide, a flexible 6-aminohexanoic acid linker and a cysteine residue was added, while to another peptide, bromoacetyl group was added. The nucleophilic thiol residue of cysteine reacts with the bromide group, forming thioether-linked transmembrane hairpins. Attempts to produce these hairpins in various solvent systems have indicated that by dissolving the transmembrane peptides in C14SB, we can obtain thioether-ligated transmembrane hairpin. Oxidation of the reactive thiol groups, however, seems to be responsible for the low ligation yield observed.